Peran Kegiatan Istigatsah dalam Meningkatkan Nilai-Nilai Keimanan di Pondok Pesantren Tremas Pacitan - Achmad Ridlowi (Transformasi : Jurnal Studi Agama Islam, 2017)
The activity of istighathah in Pesantren Tremas Pacitan in improving the values of faith can serve as a tool of our lust control so that we are always in the way of Allah SWT, can change khuluqiyah or santri personality to be better, and as a tool or a way to sharpen vision and inner view Which can awaken the santri and prompt him to abandon bad deeds to return to God when he slips and diverges from the truth.Factors that support the implementation of istighathah activities in Pondok Pesantren Tremas Pacitan is a strong santri desire to get closer to Allah SWT, teacher motivation, alumni, and society to istighathah activity, a conducive cottage environment. While the factors that hamper the implementation of istighathah activities in Pondok Pesantren Tremas Pacitan is the lack of control from the board because all administrators also follow istighathah activities, the limited facilities and infrastructure so that istighathah activities less than the maximum, the awareness of students who are less disciplined, the background of santri heterogeneous.